Liminality and developmental process of learning advantage of newness of early internationalizing firms - Kusi Appiah, Emmanuel; Galkina, Tamara; Gabrielsson, Peter (Elsevier, 2023)
Extant internationalization studies have devoted limited attention to the dynamics of the learning advantage of newness (LAN), which we, in response, investigate through the process approach and the novel lens of the concept of liminality. We conduct a longitudinal multiple-case study of five Finnish internationalizing firms. We inductively derive a process model that shows how the underlying liminal factors, such as international opportunity scaffolding activities, learning from communitas, and rituals, contribute to the development of learning advantage of newness. Originating in anthropology, the liminality perspective offers a novel perspective on LAN of early internationalizing firms. We also provide directions for future research and recommendations for practitioners.
Keywords: Early internationalization; Learning advantage of newness; Adaptive behavior; liminality; fi=Kansainvälinen liiketoiminta|en=International Business|